PENINGKATAN MANAJEMEN DAN STRATEGI BISNIS PADA UMKM DESA WARNASARI, KABUPATEN BANDUNG - Sutrisno, Niantoro; Tarto; Astuti, Enny Diah; Utami, Rahayu Tri; Primarni, Amie (POLITEKNIK LP3I JAKARTA, 2025)
The existence of Micro, Small adn Medium Enterprises (UMKM) can create jobs and empower households to earn income. UMKM have a very large role in economic growth, as aprovider of jobs and also as a source of income for the community. Therefore, empowerment is needed so that UMKM can develop further and be able to support the stability of the national economy. The development of the era, technology and competition in the business world which is getting higher every day makes UMKM actors have to have a good business strategy to be able to compete with their competitors. Various problems in running a business occur in today’s economy. The millenial generation has a differnt perspective from the previous generation. Their purchasing power is needed not like the generation above them who are more established, but they can get goods and services that are much cheaper. Several aspects play an important role in determining consumer purchasing power. This community service activity is carried out to help UMKM in Warnasari Village, Bandung regency in facing sompetition in the digital era. By learning about daily financial managment, conducting digital promotions, and also knowing how to determine the ideal selling price.